Effects of buffer properties on cyclodextrin glucanotransferase reactions and cyclodextrin production from raw sago (cycas revoluta) starch - Kamaruddin, Kamarulzaman; Md. Illias, Rosli; Abdul Aziz, Suriani; Said, Mamot; Hassan, Osman (Portland Press Ltd., 2005)
Results from the present study have shown that the ionic species of buffers, pH values and reaction temperature can affect the enzyme unit activities and product specificity of ToruzymeÂ® (Novo Nordisk A/S Bagsvaerd, Denmark) CGTase (cyclodextrin glucanotransferase). Applying a similar reaction environment (acetate buffer, pH 6.0; temperature, 60 Â°C), the CGTase was found to be capable of producing pre dominantly Î²-cyclodextrin from either raw or gelatinized sago (Cycas revoluta) starch. Changing the buffer from acetate to phosphate reduced the yield of Î²-cyclodextrin from 2.48 to 1.42 mg/ml and also affected the product specificity, where production of both Î±- and Î²-cyclodextrins were more pronounced. The decrease in the production of cyclodextrins in phosphate buffer was significant at both pH 6.0 and 7.0. However, changing the buffer to Tris/HCl (pH 7.0) showed a significant increase in Î²-cyclodextrin production. Increasing the ionic strength of sodium acetate and Tris/HCl buffers at pH 6.0 and 7.0 to equivalent ionic strength of phosphate buffers showed no significant effects on cyclodextrin production. Higher yield of cyclodextrins at pH 7.0 when Tris/ HCI was used might be due to the binding of chloride ions at the calcium-binding sites of the CGTase, resulting in the shift of the optimum pH close to physiological environment, leading to an increase in the activities and specificity.